Study of identification and simulation of ecological zoning through integration of landscape ecological risk and ecosystem health - Peng, Huaizhen; Lou, Huachao; Zhang, Yali; Wang, Weiwei; He, Qingying; Liu, Polang; Yang, Ying (Frontiers in Ecology and Evolution, 2025)
IntroductionRapid urbanization has driven extensive land use changes, thereby undermining the stability and sustainability of ecosystems. This highlights the need for refined ecological zoning to strengthen environmental governance and spatial management in urban agglomerations.MethodsThis study uses the Changsha–Zhuzhou–Xiangtan urban agglomeration as a case study, a rapidly urbanizing region in central China that lies at the intersection of montane and lowland ecosystems, making it highly sensitive to both urbanization and climate-induced changes. It examines the spatiotemporal evolution of landscape ecological risk (LER) and the ecological health index (EHI) in response to land use changes from 2000 to 2020 and subsequently delineates ecological zoning. Furthermore, it simulates future land use changes under multiple scenarios for the period 2030–2050 to assess the dynamics of future zoning.ResultsFrom 2000 to 2020, forest remained the dominant land use, followed by cultivated land and construction land. During this period, 1,029.37 km² of cultivated land and 890.88 km² of forest were converted. The total converted area of cultivated land remained relatively stable across both phases. LER was primarily concentrated at medium and medium–low risk levels. The areas classified as low, medium–low, and medium risk decreased in both phases, with reductions of 784.24 km² in the early period and 3,266.91 km² in the later period. The EHI values declined from 0.555 in 2000 to 0.543 in 2010 and 0.518 in 2020. Forest, water body, and grassland all exhibited downward trends, while construction land showed the most pronounced decline, with a 22.15% reduction. Between 2000 and 2020, the spatial overlap between ecological zones and legally protected areas shifted notably. The ecological control zone transitioned 19,875 km² to the Strict ecological conservation zone and 18,175 km² to the ecological enhancement zone. Under future scenarios, the ecological control zone is projected to expand, with hotspots extending significantly and cold spots contracting slightly. By contrast, Ecological conservation zones are expected to shrink, with hotspots becoming more fragmented and cold spots declining more substantially.ConclusionsThis study offers a scientific foundation for ecological zoning management, supporting coordinated regeneration and the sustainable development of human–land systems in rapidly urbanizing regions.